2019
DOI: 10.1051/0004-6361/201935105
|View full text |Cite
|
Sign up to set email alerts
|

GaiaDR2 reveals a star formation burst in the disc 2–3 Gyr ago

Abstract: We use Gaia data-release 2 (DR2) magnitudes, colours, and parallaxes for stars with G<12 to explore a parameter space with 15 dimensions that simultaneously includes the initial mass function (IMF) and a non-parametric star formation history (SFH) for the Galactic disc. This inference is performed by combining the Besançon Galaxy Model fast approximate simulations (BGM FASt) and an approximate Bayesian computation algorithm. We find in Gaia DR2 data an imprint of a star formation burst 2-3 Gyr ago in the Galac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
142
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 38 publications
(62 reference statements)
33
142
2
Order By: Relevance
“…This is consistent with the results of Rowell (2013) and Vergely et al (2002), as shown in the left-hand panel of Figure 10, who see an increase in star formation between 2 and 3 Gyr and a resulting decrease in the vicinity of 6 Gyr. This result is also in line with the recent work by Mor et al (2019), who compared simulations of the Besançon Galactic model with the colors, magnitudes, and parallaxes from Gaia DR2, which shows a burst of star formation between 2 and 3 Gyr in the past. The slight bimodality suggested by Figure 11 is, however, not seen in the GCE models of Snaith et al (2014) andToyouchi &Chiba (2018), as seen in the right-hand panel of Figure 10.…”
Section: Effect Of Star Formation Prescriptionsupporting
confidence: 91%
“…This is consistent with the results of Rowell (2013) and Vergely et al (2002), as shown in the left-hand panel of Figure 10, who see an increase in star formation between 2 and 3 Gyr and a resulting decrease in the vicinity of 6 Gyr. This result is also in line with the recent work by Mor et al (2019), who compared simulations of the Besançon Galactic model with the colors, magnitudes, and parallaxes from Gaia DR2, which shows a burst of star formation between 2 and 3 Gyr in the past. The slight bimodality suggested by Figure 11 is, however, not seen in the GCE models of Snaith et al (2014) andToyouchi &Chiba (2018), as seen in the right-hand panel of Figure 10.…”
Section: Effect Of Star Formation Prescriptionsupporting
confidence: 91%
“…The excesses around M bol ∼ 9 -10 could be due to recent bursts of star formation not resolved by the present binning of the massive luminosity function and, as mentioned before, deserves a detailed analysis. Figure 9 also shows that values of g ae > ∼ 3 × 10 -13 are not compatible with the results obtained by Mor et al (2019).…”
Section: The Luminosity Functionmentioning
confidence: 54%
“….48 × 10 -13 , respectively. The red line corresponds to the star formation rate obtained by Mor et al (2019).…”
Section: The Luminosity Functionmentioning
confidence: 99%
See 2 more Smart Citations